Auditing of Environmental Management in Industrial Zones of Vietnam Case Study of Industrial Zones in Lao Cai Province - Hien, Tran Thi; Hieu, Nguyen Khac; Duong, Tran Dinh; Hanh, Nguyen Thi Hong; La, Ngo Thi Thuy (Archives of Business Research, 2022)
Vietnam is a developing country with an economic growth rate among the top in Asia, therefore facing pressures from industrialization, urbanization, and population growth means that the amount of waste also increases. In the face of current environmental issues, an environmental audit is considered a tool to provide information about the environment, and a basis for assessing the possibility of environmental risks caused by enterprises, the environmental obligations of the business, as well as the degree of satisfaction with environmental standards or regulations. Besides, an environmental audit is also one of the supporting tools for harmoniously solving the relationship between economic development and environmental protection, contributing to raising the awareness of individuals and production organizations in sustainable environmental protection. The article focuses on analyzing and evaluating the current status of environmental management in industrial zones in Lao Cai province based on content and audit criteria for the period 2017-2020. From there, it proposes some recommendations to improve the efficiency of environmental management and protection in Lao Cai in the coming time.